Effect of titanium dioxide nanotubes on the mechanical and antibacterial properties of the low-viscosity bulk-fill composite - Ozlen, Rumeysa Hatice Enginler; Dalkilic, Evrim Eliguzeloglu; Kucukyildirim, Bedri Onur; Eker, Aysegul Akdogan; Topcuoglu, Nursen; Kulekci, Guven (TAYLOR & FRANCIS LTD, 2022)
The purpose of this investigation is to determine the impact of titanium dioxide nanotubes (TiO2-n) on the mechanical and antibacterial properties of bulk-fill composite resin. TiO2-n were synthesized in laboratory conditions using the hydrothermal method. Varying amounts of TiO2-n were included in the bulk-fill composite resin. Microhardness, surface roughness, and the three-point bending test were used to determine the mechanical properties of the composite. After the flexural strength test, the fractured surfaces of the composite resin were examined with a high-resolution scanning electron microscope. The antibacterial activity of Streptococcus mutans (S.mutans) and Lactobacillus Casei (L.casei) was assessed using a direct contact test. The statistical examination was completed using IBM SPSS Statistics 22. Group differences were compared using the Kruskal Wallis and Dunn tests (p 0.05). Adding 0.5% and 1% TiO2-n increased the microhardness of the bulk-fill composite (p 0.05). Though adding TiO2-n did not have an antibacterial impact on S.mutans (p > 0.05), adding 0.5% TiO2-n produced an antibacterial impact on L.casei in daylight (p < 0.05). The addition of 0.5% and 1% TiO2-n increased the microhardness of the top surface of the bulk-fill composite without negatively affecting surface roughness or the composite's three-point bending properties Adding 0.5% TiO2-n to the composite resin produced an antibacterial impact on L.casei in daylight.
Keywords: TiO2-n; nanotube; bulk-fill composite resin; three-point bending; microhardness; surface roughness; POLYMERIZATION SHRINKAGE; DENTAL COMPOSITE; CURE; RESTORATIONS; FAILURE; REASONS; DEPTH; TEETH; Engineering; Materials Science; Mechanics